Improving Public–Private Partnership Mechanisms For Infrastructure Development In The Regions: A Cross-Country Empirical Assessment With Evidence From Uzbekistan - Alisher BAYMIRZAEV (The Journal of Interdisciplinary Human Studies, 2026)
Public–private partnerships (PPPs) are widely promoted as an instrument for closing regional infrastructure gaps in developing economies. This article asks whether the observed structure of global private infrastructure flows is compatible with that role. Using the World Bank Private Participation in Infrastructure database for 2024, merged with World Bank governance and national accounts data, a cross-section of 55 low- and middle-income economies is analysed by means of concentration measures, distributional statistics and ordinary least squares estimation with heteroscedasticity-consistent standard errors. Three findings emerge. First, private infrastructure flows are extremely concentrated: the five largest recipients absorb 70.9 per cent of global commitments, and the Gini coefficient across recipients reaches 0.829. Second, flows are sectorally concentrated in large, revenue-generating national assets energy accounts for 67.5 per cent and information and communication technology for 10.4 per cent of commitments, while water, sanitation and municipal solid waste, the sectors that constitute regional and local infrastructure, together receive 1.6 per cent. Third, flows are lumpy: 36.4 per cent of recipient economies closed exactly one project in 2024 and the median recipient closed two, with a median project size of US$109 million. Regulatory quality does not explain flow intensity conditional on participation, but weaker regulatory environments are systematically associated with dependence on development-finance risk mitigation.